Integrating Innovation Capability, Knowledge Management, and Digital Leadership for Organizational Sustainability: A Systematic Literature Review - Temi Delizar Hudoyo; Supardi Tahir (Dinasti Publisher, 2026)
Organizational Sustainability has become a strategic priority for organizations seeking long-term competitiveness amid rapid digital transformation and increasing environmental and social challenges. Although Innovation Capability, Knowledge Management, and Digital Leadership are recognized as critical organizational capabilities supporting sustainable performance, previous studies have predominantly examined these capabilities independently. Consequently, limited understanding exists regarding their integrated contribution to Organizational Sustainability.This study systematically reviews the existing literature on the relationships among Innovation Capability, Knowledge Management, Digital Leadership, and Organizational Sustainability using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA 2020) guidelines. A total of twenty-four peer-reviewed studies were selected and analyzed through qualitative thematic synthesis to identify dominant research themes, theoretical perspectives, empirical findings, and research gaps. The review indicates that Innovation Capability strengthens organizations' ability to develop sustainable innovations, Knowledge Management facilitates organizational learning and knowledge integration, and Digital Leadership enables strategic digital transformation that supports long-term sustainability. However, the literature remains fragmented because these capabilities are rarely examined within a unified framework. This study proposes an integrated capability-based perspective that combines these three organizational capabilities to explain Organizational Sustainability, while offering theoretical insights, managerial implications, and directions for future research.